A Hybrid Analysis to Detect Java Serialisation Vulnerabilities - Rasheed, Shawn; Dietrich, Jens (2020 35th IEEE/ACM International Conference on Automated Software Engineering (ASE), 2020)
Serialisation related security vulnerabilities have recently been reported for numerous Java applications. Since serialisation presents both soundness and precision challenges for static analysis, it can be difficult for analyses to precisely pinpoint serialisation vulnerabilities in a Java library. In this paper, we propose a hybrid approach that extends a static analysis with fuzzing to detect serialisation vulnerabilities. The novelty of our approach is in its use of a heap abstraction to direct fuzzing for vulnerabilities in Java libraries. This guides fuzzing to produce results quickly and effectively, and it validates static analysis reports automatically. Our approach shows potential as it can detect known serialisation vulnerabilities in the Apache Commons Collections library.